2016
DOI: 10.1614/wt-d-15-00076.1
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pigweed (Amaranthusspp.) in Glufosinate-Resistant Soybean in the Midwest and Mid-South

Abstract: Pigweeds are among the most abundant and troublesome weed species across Midwest and mid-South soybean production systems because of their prolific growth characteristics and ability to rapidly evolve resistance to several herbicide sites of action. This has renewed interest in diversifying weed management strategies by implementing integrated weed management (IWM) programs to efficiently manage weeds, increase soybean light interception, and increase grain yield. Field studies were conducted across 16 site-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 36 publications
(56 reference statements)
6
29
0
Order By: Relevance
“…Further research across the Midwest and Midsouth indicated that narrow-row soybean and a high soybean seeding rate increased canopy coverage, resulting in reduced end-of-season Amaranthus spp. growth characteristics, including height, biomass, and seed production, but A. tuberculatus density was not impacted (Butts et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Further research across the Midwest and Midsouth indicated that narrow-row soybean and a high soybean seeding rate increased canopy coverage, resulting in reduced end-of-season Amaranthus spp. growth characteristics, including height, biomass, and seed production, but A. tuberculatus density was not impacted (Butts et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…More uniform spatial arrangement in soybean contributes to decreased intraspecific competition, improved resource capture, rapid canopy closure (Légère and Schreiber 1989; Willcott et al 1984), more complete light interception throughout the growing season (Dalley et al 2004; Taylor et al 1982), reduced photosynthetic photon flux density beneath the soybean canopy (Green-Tracewicz et al 2012), and greater soybean interference with weeds (Yelverton and Coble 1991). As a result, reduced soybean row spacing and/or increased seeding densities can reduce weed population densities (Nice et al 2001), late-season weed recruitment (Harder et al 2007), biomass accumulation (Arce et al 2009; Rich and Renner 2007), seed production (Butts et al 2016; Nice et al 2001), and seedbank inputs (Chandler et al 2001). For example, greater population densities of soybean (~676,000 plants ha −1 ) combined with narrow-row spacing (19 cm) reduced sicklepod [ Senna obtusifolia (L.) H. S. Irwin & Barneby] population densities by up to 80% compared with low soybean densities (~245,000 plants ha −1 ) in wide rows (76 cm) (Nice et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of using herbicide mixtures are well documented, including season-long weed control and a reduction in the risk of herbicide resistance (Beckie and Reboud 2009;Butts et al 2016;Johnson et al 2012;Kumar and Jha 2015;Loux et al 2011).…”
mentioning
confidence: 99%